ANALYSIS OF ANDROID BASED PALEMBANG BIBIK SAYUR APPLICATION USING USABILITY TESTING - Muhamad Ariandi; Muhammad Naufal Risqi (Jurnal Teknik Informatika (Jutif), 2022)
The Bibik Sayur application is an application-based online grocery shopping owned by Palembang people, who are already very familiar with telecommunications technology. One of them is by using this application, it invites people to shop from home with quality goods and low prices. Moreover, in the midst of the spread of Covid-19, they have to face the crowd to find the quality goods they want. The problem that exists in this research is that the Bibik Sayur Application does not yet know the extent of the community's level of utility in using the Bibik Sayur Application service. From these problems, the Bibik Sayur application needs to be evaluated using usability testing which is a process where the software is tested to see how useful it is for the user, and if the user or user is satisfied with the software, it can be concluded that the application can be used properly. To measure usability testing on the Bibik Sayur Application, there are five usability aspects used, namely Learnability (easy to learn), Efficiency (efficiency), Memorability (easy to remember), Errors (error and security) and Satisfaction (satisfaction). The results showed the measurement of usability testing in all aspects, the score obtained was 84%. Based on the feasibility measurement scale, the value between the scale of 81-100 means that the Bibik Sayur Android application is very suitable for use by the people of the Sako sub-district, Sialang village.